2015
DOI: 10.1371/journal.pone.0124936
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 Up-Regulates MiR-21 and the MiRNAs Hosted in the CLCN5 Gene in Chronic Lymphocytic Leukemia

Abstract: Interleukin 4 (IL-4) induces B-cell differentiation and survival of chronic lymphocytic leukemia (CLL) cells. MicroRNAs (miRNAs) regulate mRNA and protein expression, and several miRNAs, deregulated in CLL, might play roles as oncogenes or tumor suppressors. We have studied the miRNA profile of CLL, and its response to IL-4, by oligonucleotide microarrays, resulting in the detection of a set of 129 mature miRNAs consistently expressed in CLL, which included 41 differentially expressed compared to normal B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 50 publications
0
41
1
Order By: Relevance
“…40 CLL cells express high levels of miR-29a and miR-29b. 40,41 M-CLL cells express more miR-29a and miR-29b than U-CLL cells. This expression pattern is negatively correlated with CD79b protein.…”
Section: Discussionmentioning
confidence: 98%
“…40 CLL cells express high levels of miR-29a and miR-29b. 40,41 M-CLL cells express more miR-29a and miR-29b than U-CLL cells. This expression pattern is negatively correlated with CD79b protein.…”
Section: Discussionmentioning
confidence: 98%
“…17,19,50,51 Increased miR-34a levels have been noted in several CLL studies. 26,29,52,53 Inhibition of miR-34a by antisense RNA has been shown to sensitize lymphoma cells to apoptosis. 54 We found that levels of miR-34a were 87-fold higher in circulating CLL cells in comparison to normal circulating B-cells; and miR-34a was significantly higher in CLL cells in the lymph node than that in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…They reported the upregulation of several miRNAs in CLL, including miR-144-5p, miR-144-3p, miR-28-5p, miR-486-5p, and miR-486-3p. These miRNAs were regulated by IL-4 in CLL [61]. Another study by Gao C et al using bioinformatics analysis identified miRNA-mRNA target pairs in CLL.…”
Section: Mir-144 In Chronic Lymphocytic Leukemiamentioning
confidence: 96%